Smallfoot [videorecording (Blu-Ray + DVD)] - Sera, Clare; Kirkpatrick, Karey (Warner Home Video, 2018)
A bright young yeti finds something he thought didn't exist: a human. News of this throws the simple yeti community into an uproar over what else might be out there in the big world beyond their snowy village, in an all-new story about friendship, courage, and the joy of discovery.